Application of MoWS2-rGO/PVA thin film as all-fiber pulse and amplitude modulators in the O-band region - Ahmad, Harith; Aidit, Siti Nabila; Tiu, Zian Cheak; Ooi, Shok Ing (Elsevier, 2019)
In this work, a MoWS2-rGO/PVA thin film is fabricated and its applications as in amplitude modulation are demonstrated. Embedded in a praseodymium fluoride fiber laser cavity, the MoWS2-rGO/PVA thin film is able to induce pulsing in the laser output, which operates in the O-band region. As an optical amplitude modulator, the MoWS2-rGO/PVA thin film is capable of achieving a modulation efficiency of 0.17 dB/mW in the O-band region over a pump power range of 46.0 mW to 78.5 mW. C-band and L-band operation is also demonstrated, with modulation efficiencies of 0.30 dB/mW and 0.15 dB/mW, respectively over pump power ranges of 3.51 mW–52.17 mW and 24.4 mW–61.3 mW. This work can be improved by further engineering the composition ratio of the alloy material to enhance the modulation efficiency for both pulsed and amplitude modulations, giving rise to various applications, in particular in bio-medicine and manufacturing.